The Knot's yours truly : inspiration and ideas to personalize your wedding - Roney, Carley (Clarkson Potter, 2017)
"Your wedding day is a unique opportunity to show the world just who you are as a couple. The Knot's Yours Truly helps you envision your celebration--from the big pieces like location to the small stuff like flatware--and shine a spotlight on your particular style. Chock-full of innovative details, plus tangible ideas for your ceremony, escort cards, wedding cake, The Knot's Yours Truly also includes 20 craft projects for personalizing your day. From invitation embellishments to a macrame leash for your four-legged ring bearer, this book has everything you need for the most extraordinary day"--